The Spatial Effect of Police Foot Patrol on Crime Patterns: A Local Analysis - Andresen, Martin A. (International journal of offender therapy and comparative criminology, 2019)
A foot patrol program was implemented in Lower Lonsdale, British Columbia, in the summer of 2010 and continues today. As a part of assessing the foot patrol's effect on crime in the neighbourhood, the spatial similarity was examined by comparing the crime pattern before the foot patrol initiative (2007-2009) with the crime pattern during the foot patrol program (2010-2012). Considering these baseline and treatment data sets and a spatial point pattern test, the spatial similarity between two data sets is analyzed. In general, the continued presence of foot patrol appears to have created a concentration of crime in specific areas, rather than a diffusion effect. The areas that continued to experience increased crime during foot patrol presence were often in the catchment area, suggesting displacement does occur, or along the border between the catchment and primary patrol area.